Filolosofi Ki Hadjar Dewantara: Bimbingan Kelompok Teknik Simulasi Permainan Yang Menyenangkan - Agustam; Prasetya, Ahmad Fajar (CV. SINAR HOWUHOWU, 2025)
Group guidance is one of the services within guidance and counseling that plays a strategic role in developing students’ potential, particularly through constructive social interaction dynamics. This article discusses the application of enjoyable game-based simulation techniques in group guidance grounded in the philosophy of Ki Hadjar Dewantara, which emphasizes the principles of among, the tri-center of education, and the appreciation of learners’ natural and developmental characteristics. The purpose of this study is to describe the effectiveness of game simulations as a group guidance strategy to enhance students’ activeness, cooperation, and emotional engagement in social learning processes. This study employs a descriptive qualitative approach, with observation, interviews, and documentation as data collection techniques. The results indicate that games designed according to students’ developmental stages are able to create a free, joyful, and meaningful atmosphere, encouraging active participation without pressure. Furthermore, the educational values of Ki Hadjar Dewantara are reflected in the guidance process through the cultivation of mutual respect, self-awareness, and collective responsibility. The game simulations also improve communication skills, problem-solving abilities, and reduce students’ tendency to exhibit passive behavior. Thus, enjoyable game simulation techniques can be recommended as an innovative method in group guidance services that align with national educational philosophy. These findings are expected to serve as a reference for guidance and counseling teachers in designing creative, humanistic, and character-oriented group guidance activities.